FAKTOR-FAKTOR YANG MEMPENGARUHI HASIL BELAJAR IPS TERPADU SISWA SMP NEGERI 5 PADANG TAHUN AJARAN 2012/2013 - Mardatila, Mardatila; Ahmad, Ridwan; Zahara, Leni (STKIP PGRI Sumbar, 2013)
This study aims to determine empirically, concerning: (1) the influence of motivational variables on learning Result (2) parental attention on learning result (3) the influence of the student interest in learning to the learning result of the students in SMP N 5 Padang (4) the influence of motivation, parentâs attention and student interest in learning to the studentâs learning result. This study is a correlation description research. The Research samples are the student population of SMP N 5 Padang totaling 842 respondents, were taken proportional sampling randomly in every classroom, so that the sample of the respondents are as many as 89 students. Based on the analysis of data using the simple linear regression and the multiple linear regression, using the statistical program SPSS version 12, it is obtained the following results: There is a significant relationship between learning motivation to theÂ learning result of the Social Science Integrated students in SMP Negeri 5 Padang, because t count> t table (7.018> 2.000), relationship between the learning motivation with the student learning result of the Social Science Student of SMP Negeri 5 Padang is included low (r = 0.601) and the contributions that is made is 36.1%. There is a significant influence between parental attention to the learning result of the Social Science student in SMP Negeri 5 Padang, because t count> t table (4.214> 2.000), the relationship between the parental attention with the learning result of the social science integrated student in SMP Negeri 5 Padang is included medium (r = 0.412) and the contributions that is made is 16.9%. A significant influence between the students interest in learning with the learning result of the Social Science integrated students of SMP Negeri 5 Padang, because t count> t table (3.609> 2.000), the relationship between the students interest in learning with the learning result of Social Science Integrated student of the student in SMP Negeri 5 Padang included low (r = 0.361) and contribution that is made is 13%. There is a significant influence between learning motivation, parental attention and the student interest in learning with the learning result of Social Science Integrated students in SMP Negeri 5 Padang, because F count > F table (16.281> 2.72), the relationship among learning motivation, parental concern and student interest in learning together with the learning result of the Social Science Integrated Student in SMP Negeri 5 Padang is strong (r = 0.604) and the contributions that is made is 36.5%.